2D WS2 co-catalysts induce the growth of CdS and enhance the photocatalytic performance. Issue 25 (17th June 2021) - Ma, Wenxuan; Hao, Shuhua; Zhang, Lei; Lv, Baoyi; Zhao, Gang; Huang, Jinzhao; Xu, Xijin
Abstract : Here, we obtain WS2 nanosheets with near-infrared absorption which can replace the precious metal Pt as excellent cocatalysts. Abstract : CdS is widely used in the field of photocatalysis owing to its excellent photocatalytic H2 evolution (PHE) activity, but the photocatalytic stability of CdS is inhibited because of the drawback of photocorrosion. Under light, the introduction of WS2 cocatalysts induces the growth of layered CdS on the WS2 nanosheets. Through the photocatalytic activity measurement, after adding ultrathin WS2 nanosheets, the amount of H2 released can reach 139.15 mmol g −1 after 7 h, which is 11.3 times higher than that of pure CdS nanoparticles. Furthermore, these composites illustrate excellent light absorption performance in the near-infrared region. A heterojunction is formed between WS2 and CdS under light, which greatly promotes the mobility of interface carriers and limits the recombination of photogenerated carriers. The hydrogen evolution output remains stable after 42 h, and the photocorrosion problem is effectively suppressed. In this work, we provide an effective and simple method to improve photocatalytic activity and stability, which is beneficial to the practical development of photocatalysis.